UM MAIS UM SÃO DOIS? ANÁLISE DE GÊNEROS DISCURSIVOS EM MANUAIS DE MATEMÁTICA FINANCEIRA - Pinheiro, Ana Paula Freb (2020)
In this study, the main objective is the analysis of genres instantiated in Didactic manuals used to teach Financial Mathematics in courses in the area of Social Sciences at a private university in Santa Maria / RS. To achieve this goal, we used the theoretical-methodological approach of Systemic-Functional Linguistics (LSF) and studies on the gender analysis of the Sydney School. The corpus consists of three didactic manuals of the Financial Mathematics discipline, of which we cut out to work with the contents of simple interest and compound interest. With regard to the registration variables, the field is represented in 48 text units, whose social activity aims to teach a certain content, through a verbal language with the presence of formulas, tables and graphs, with specific technical terms of Mathematics Financial (mode). The relations variable does not show proximity between author and reader, as the text lacks linguistic elements that perform this function. There is a prevalence of the Ideation and Conjunction categories in most text units and the results point to genres of the family of explanations, procedures and reports. In addition, we also raised the possibility of a macrogenre instantiated in the corpus under analysis.